Levendegørelse og publikumsdeltagelse - Vatne, Ingrid (Peripeti, 2011)
Based upon a comparative analysis of two dramatized tours, Lys i Mørket (eng.: Light, The Old Town open-air Museum, Denmark) and the Dungeon (Warwick Castle, England), Vatne discusses dramaturgical strategies in museum communication with a focus on how the visitor-participation contributes to the process of meaning.